Uji Toksisitas Akut Ekstrak Air Dan Ekstrak Etanol Daun Kacapiring (Gardenia jasminoides Ellis) Terhadap Larva Artemia Salina Leach Dengan Metode Brine Shrimp Lethality Test (BSLT) - Nuralifah, Nuralifah; Parawansah, Parawansah; Nur, Hasniana (Jurusan Farmasi Universitas Negeri Gorontalo, 2021)
A toxicity test is a test to detect the toxic effect of a substance on a biological system and to obtain typical dose-response data from the test preparation. This study aims to determine the content of secondary metabolites from the aqueous extract and ethanolic extract of gardenia leaves, characterization of gardenia leaf extract, and acute toxicity using the BSLT method against Artemia salina Leach shrimp larvae.Phytochemical screening tests were carried out by the color change method which included the alkaloid test, flavonoid test, tannin test, saponin test, and terpenoid test. Extract characterization tests include determination of water-soluble extract, determination of ethanol-soluble extract, determination of water content, and determination of ash content. Acute toxicity test using the Brine Shrimp Lethality Test (BSLT) method using Artemia salina Leach shrimp larvae.The results of the phytochemical screening test for the aqueous extract of gardenia leaves showed positive results on saponins, while the phytochemical screening tests on ethanol extracts showed positive results on alkaloids, flavonoids, saponins, tannins, and terpenoids. The results of the characterization test on the aqueous extract of gardenia leaves were that the ethanol-soluble extract content was 20.19%, the water-soluble extract content was 23.17%, the water content was 99.13% and the ash content was 0.29%. Meanwhile, in the ethanolic extract of gardenia leaves, the ethanol-soluble extract content was 60.80%, the water-soluble extract content was 57.14%, the water content was 7.87% and the ash content was 3.22%. The results show that gardenia leaves are not toxic with the LC50 value of the water extract of the gardenia leaves is 1399.64 g/mL and the LC50 value of the ethanolic extract of the gardenia leaves is 1080.96 so that it can be used as traditional medicine.